Intramuscular Compartment Pressure Measurement in Chronic Exertional Compartment Syndrome: New and Improved Diagnostic Criteria. (February 2015) - Roscoe, David; Roberts, Andrew J.; Hulse, David
Background: Patients with chronic exertional compartment syndrome (CECS) have pain during exercise that subsides with rest. Diagnosis is usually confirmed by intramuscular compartment pressure (IMCP) measurement. Controversy exists regarding the accuracy of existing diagnostic criteria. Purpose: (1) To compare dynamic IMCP measurement and anthropometric factors between patients with CECS and asymptomatic controls and (2) to establish the diagnostic utility of dynamic IMCP measurement. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: A total of 40 men aged 21 to 40 years were included in the study: 20 with symptoms of CECS of the anterior compartment and 20 asymptomatic controls. Diagnoses other than CECS were excluded with rigorous inclusion criteria and magnetic resonance imaging. The IMCP was measured continuously before, during, and after participants exercised on a treadmill, wearing identical footwear and carrying a 15-kg load. Results: Pain experienced by study subjects increased incrementally as the study progressed ( P < .001). Pain levels experienced by the case group during each phase of the exercise were significantly different ( P = .021). Subjects had higher IMCP immediately upon standing at rest compared with controls (23.8 mm Hg [controls] vs 35.5 mm Hg [subjects]; P = .006). This relationship persisted throughout the exercise protocol, with the greatest difference corresponding to the period of maximal tolerable pain (68.7 mm Hg [controls] vs 114 mm Hg [subjects]; P < .001). Sensitivity and specificity were consistently higher than the existing criteria with improved diagnostic value (sensitivity = 63%, specificity = 95%; likelihood ratio = 12.5 [95% CI, 3.2-49]). Conclusion: Anterior compartment IMCP is elevated immediately upon standing at rest in subjects with CECS. In patients with symptoms consistent with CECS, diagnostic utility of IMCP measurement is improved when measured continuously during exercise. A cutoff of 105 mm Hg in phase 2 provides better diagnostic accuracy than do the Pedowitz criteria of 30 mm Hg and 20 mm Hg at 1 and 5 minutes after exercise, respectively.